High Elmo1 expression aggravates and low Elmo1 expression prevents diabetic nephropathy - Hathaway, Catherine K. (Proc Natl Acad Sci U S A, 2016)
Human genome-wide association studies have demonstrated that polymorphisms in the engulfment and cell motility protein 1 gene (ELMO1) are strongly associated with susceptibility to diabetic nephropathy. However, proof of causation is lacking. To test whether modest changes in its expression alter the severity of the renal phenotype in diabetic mice, we have generated mice that are type 1 diabetic because they have the Ins2(Akita) gene, and also have genetically graded expression of Elmo1 in all tissues ranging in five steps from ∼30% to ∼200% normal. We here show that the Elmo1 hypermorphs have albuminuria, glomerulosclerosis, and changes in the ultrastructure of the glomerular basement membrane that increase in severity in parallel with the expression of Elmo 1. Progressive changes in renal mRNA expression of transforming growth factor β1 (TGFβ1), endothelin-1, and NAD(P)H oxidase 4 also occur in parallel with Elmo1, as do the plasma levels of cystatin C, lipid peroxides, and TGFβ1, and erythrocyte levels of reduced glutathione. In contrast, Akita type 1 diabetic mice with below-normal Elmo1 expression have reduced expression of these various factors and less severe diabetic complications. Remarkably, the reduced Elmo1 expression in the 30% hypomorphs almost abolishes the pathological features of diabetic nephropathy, although it does not affect the hyperglycemia caused by the Akita mutation. Thus, ELMO1 plays an important role in the development of type 1 diabetic nephropathy, and its inhibition could be a promising option for slowing or preventing progression of the condition to end-stage renal disease.